Numerical investigation of nucleate pool boiling outside a vertical tube under sub-atmospheric pressures. (July 2020) - Ren, Shuai; Zhou, Wenzhong
Abstract: In this paper, nucleate pool boiling outside a vertical tube under sub-atmospheric pressure conditions has been numerically studied. The volume-of-fluid interface tracking technique is implemented on the basis of a two dimensional axis-symmetric Eulerian-Eulerian multiphase framework. The phase change model is applied into a computational fluid dynamics platform by user-defined functions. The numerical model results are compared with experimental data at both atmospheric and sub-atmospheric pressures, and good agreement is obtained. From the validation results, the logarithm of the mass transfer coefficient is linear to saturation temperature and wall heat flux, respectively. The simulations are performed under operating pressure of 1–10 kPa, heat flux from 22.4 to 77.7 kW/m 2, and liquid subcooling of 0–20 K. The effects of tube length and liquid height on the boiling heat transfer have been studied. The two-phase flow patterns and bubble behaviors under different pressure conditions were analyzed and compared. Under lower pressures, because of the increase of liquid subcooling with the liquid height, boiling occurs at the top of the tube wall firstly, and then gradually develops downwards. The bubbles keep growing while they slide upwards along the wall and coalesce with the adjacent bubbles but the bubbles will not detach from the wall until leaving the top part of the tube. The bubble sliding velocity increases with the bubble size and tube height. From the computational results, the wall superheat increases with the decreasing operating pressure and the liquid subcooling under the same heat fluxes. The required heat flux for the onset of nucleate boiling is higher for the boiling outside a vertical tube than that for the boiling on a horizontal plate. Different from the sub-atmospheric pool boiling on a horizontal surface, the heat transfer over a vertical tube is not sensitive to the change of the liquid height. Furthermore, the averaged wall temperature is higher on the longer tubes due to the severe bubble coalescence.